An emergent theory of digital library metadata enrich then filter - Alemu, Getaneh; Stevens, Brett (Chandos information professional series., 2015)
An Emergent Theory of Digital Library Metadata is a reaction to the current digital library landscape that is being challenged with growing online collections and changing user expectations. The theory provides the conceptual underpinnings for a new approach which moves away from expert defined standardised metadata to a user driven approach with users as metadata co-creators. Moving away from definitive, authoritative, metadata to a system that reflects the diversity of users' terminologies, it changes the current focus on metadata simplicity and efficiency to one of metadata enriching, which is a continuous and evolving process of data linking. From predefined description to information conceptualised, contextualised and filtered at the point of delivery. By presenting this shift, this book provides a coherent structure in which future technological developments can be considered.